A Clinico-Histopathological Study of Orbital and Ocular Lesions; a Multicenter Study - Bastola, P; Koirala, S; Pokhrel, G; Ghimire, P; Adhikari, RK (Journal of Chitwan Medical College, 2013)
The study aimed at finding out the morphological and clinico-pathological correlation of Orbital and Ophthalmic lesions in various eye institutes of Nepal. The study also aimed at finding out the prevalence of Ophthalmic lesions needing histopathological examination. This cross sectional descriptive study was carried out in various tertiary eye hospitals of Nepal from 2008 – 2012. The department of pathology was also incorporated in giving the correct histopathological findings in time. All the relevant data were entered in a specifically designed proforma for the study and analyzed. One hundred Ophthalmic and Orbital lesions were studied in various age groups. Ophthalmic and Orbital lesions were highest (18%) in 31-40 year age group patients. Eyelid (57%) was the most commonly involved site. Clinical diagnosis was consistent with histopathological diagnosis in more than 60% of the cases. Among eyelid lesions, incidence of dermoid cyst (21%) was highest. While in Conjunctival lesions, granuloma pyogenicum (22.5%) was highest followed by other lesions. A clinico-pathological diagnosis of malignant orbital tumors or ocular tumors was made in 30% of cases. While 70% cases of Ophthalmic or orbital lesions were benign in nature. All Ophthalmic lesions removed surgically should always (without exception) be subjected to histopathological examination to establish correct diagnosis for further management. However this study has shown that a good clinical examination and diagnosis before subjecting the patient for histopathological examination gives the patient and the treating surgeon a better outcome. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8442 Journal of Chitwan Medical College Vol.3(2) 2013 40-44